Social-economical decision making in current and remitted major depression. Issue 6 (10th October 2014) - Pulcu, E.; Thomas, E. J.; Trotter, P. D.; McFarquhar, M.; Juhasz, G.; Sahakian, B. J.; Deakin, J. F. W.; Anderson, I. M.; Zahn, R.; Elliott, R.
Abstract : Background: Prosocial emotions related to self-blame are important in guiding human altruistic decisions. These emotions are elevated in major depressive disorder (MDD), such that MDD has been associated with guilt-driven pathological hyper-altruism. However, the impact of such emotional impairments in MDD on different types of social decision-making is unknown. Method: In order to address this issue, we investigated different kinds of altruistic behaviour (interpersonal cooperation and fund allocation, altruistic punishment and charitable donation) in 33 healthy subjects, 35 patients in full remission (unmedicated) and 24 currently depressed patients (11 on medication) using behavioural-economical paradigms. Results: We show a significant main effect of clinical status on altruistic decisions ( p = 0.04) and a significant interaction between clinical status and type of altruistic decisions ( p = 0.03). More specifically, symptomatic patients defected significantly more in the Prisoner's Dilemma game ( p < 0.05) and made significantly lower charitable donations, whether or not these incurred a personal cost ( p < 0.05 and p < 0.01, respectively). Currently depressed patients also reported significantly higher guilt elicited by receiving unfair financial offers in the Ultimatum Game ( p < 0.05). Conclusions: Currently depressed individuals were less altruistic in both a charitable donation and an interpersonal cooperation task. Taken together, our results challenge the guilt-driven pathological hyper-altruism hypothesis in depression. There were also differences in both current and remitted patients in the relationship between altruistic behaviour and pathological self-blaming, suggesting an important role for these emotions in moral and social decision-making abnormalities in depression.